2018
DOI: 10.1016/j.msea.2018.03.108
|View full text |Cite
|
Sign up to set email alerts
|

In-situ experimental and numerical studies of the damage evolution and fracture in a Fe-TiB2 composite

Abstract: A joint experimental and modelling study of plastic strain and ensuing damage in a novel metal matrix composite (Fe-TiB 2) is presented. Damage is observed and quantified using SEM images processing and Acoustic Emission (AE) analysis. The use of AE confirms that the surface damage observed is strongly correlated to damage in the bulk of the material. The primary mode of damage is particle fracture. Very little particle decohesion is observed, indicating an exceptionally good cohesion of the steel/particle int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…The Fourier transform, which is a “time domain to frequency domain” transformation, is equivalent to a decomposition or base operation. The FFT analysis method has been widely used in the waveform signal processing of AE technology .…”
Section: Resultsmentioning
confidence: 99%
“…The Fourier transform, which is a “time domain to frequency domain” transformation, is equivalent to a decomposition or base operation. The FFT analysis method has been widely used in the waveform signal processing of AE technology .…”
Section: Resultsmentioning
confidence: 99%
“…Koohbor et al [ 33 ] and Anzelotti et al [ 34 ] applied the DIC for analysis of the meso-scale strain localization of a woven reinforced composite. In the case of the particle-reinforced composites, which are the subject of the present work, experimental results presenting deformation behavior at the level of constituents can be found in the work of Hadjem-Hamouche et al [ 35 ]. There are also several interesting papers associated with measuring the local strain fields by the DIC related to steels [ 36 , 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported that adding reinforcement into TiB2 matrix can improve its mechanical performance. These reinforcements include metallic additives (Ni [6], Fe [7], Co [8], etc.) and non-metallic additives (TiSi2 [9], MoSi2 [10], SiC [11], etc.).…”
Section: Introductionmentioning
confidence: 99%